알츠하이머병과 뇌소혈관질환의 연관성 - 이경훈; 강경미; Kyung Hoon Lee; Koung Mi Kang (Taehan Yŏngsang Ŭihakhoe chi, 2022)
Cerebral small vessel disease (CSVD) includes vascular lesions detected on brain MRI, such as white matter hyperintensities, lacunar infarctions, microbleeds, or enlarged perivascular spaces. There is accumulating evidence that vascular changes may play an important role in development of Alzheimer's disease (AD), and CSVD lesions detected on brain MRI were reported to be associated with β-amyloid and tau proteins accumulation. As the vascular contribution has therapeutic potential, it is important to understand the association of CSVD with AD and AD biomarkers. This review begins with a brief introduction of AD and AD biomarkers, explains the association between AD and vascular changes, and then details the pathogenesis and MR imaging findings of CSVD. Afterwards, we discuss the association of CSVD with AD and AD biomarkers. 뇌소혈관질환은 뇌 자기공명영상에서 흔히 관찰되는 혈관성 변화로 뇌백질 고신호강도, 뇌미세출혈, 열공성 경색, 혈관주위공간 등을 포함한다. 이러한 혈관성 변화가 알츠하이머병(Alzheimer's disease; 이하 AD)의 발병 및 진행과 관련되어 있고, 대표 병리인 베타 아밀로이드 및 타우 단백의 침착과도 연관되어 있다는 증거들이 축적되고 있다. 혈관성 변화는 생활습관 개선이나 약물 치료를 통해 예방과 개선이 가능하기 때문에 뇌소혈관질환과 AD 및 AD 생체지표의 관련성을 연구하는 것이 중요하다. 본 종설에서는 AD와 AD 생체지표에 대해 간략히 소개하고, AD와 혈관성 변화의 관련성에 대해 축적된 증거들을 제시한 다음, 뇌소혈관질환의 병태 생리와 MR 영상 소견을 설명하고자 한다. 또 뇌소혈관질환과 AD 진단의 위험도 및 AD 생체지표와의 관련성에 대한 기존 연구 결과들을 정리하고자 한다.